Development and Validation of Token Pedia: A Gamified Digital Mental Health Application for Adolescents in Islamic Boarding Schools - Nadila Kusuma Wardani; Ahmad Guntur Alfianto; Wira Daramatasia (KHD Production, 2026)
Adolescent mental health issues in Islamic boarding schools are escalating due to academic pressures, strict regulations, and pervasive stigmas. Conventional interventions remain insufficient, underscoring the need for accessible digital strategies. This study developed and evaluated